2002
DOI: 10.1034/j.1399-6576.2002.460720.x
|View full text |Cite
|
Sign up to set email alerts
|

Auditory evoked potential monitoring with the AAITM‐index during spinal surgery: decreased desflurane consumption

Abstract: Titrating depth of desflurane anesthesia using AAItrade mark-index guidance decreased main anesthetic consumption and improved emergence during spine surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A number of studies have indicated that the use of brain monitoring can decrease anaesthetic drug consumption and reduce the time required for emergence, suggesting that titrating anaesthesia according to brain monitor indices results in patients having lighter anaesthesia than those titrated according traditional clinical evaluation (7–10). Jensen recently reviewed the conceptual pitfalls and problematic lack of a gold standard when describing depth of hypnosis (11).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have indicated that the use of brain monitoring can decrease anaesthetic drug consumption and reduce the time required for emergence, suggesting that titrating anaesthesia according to brain monitor indices results in patients having lighter anaesthesia than those titrated according traditional clinical evaluation (7–10). Jensen recently reviewed the conceptual pitfalls and problematic lack of a gold standard when describing depth of hypnosis (11).…”
Section: Discussionmentioning
confidence: 99%